Timor-Leste Health Sector Review : Appendices - World Bank (Washington, DC, 2013)
The Timor-Leste health sector review describes the accomplishments made by the government of Timore-Leste in the health sector since it separated from Indonesia, and analyzes the challenges still facing the government moving forward. Infant and maternal mortality, and malnutrition, are still important battles. Underutilization of services, and poor quality of services when available, are also reasons for the poor health quality indicators. Improving the quality or effectiveness of health services is difficult. However, now that most of the basic health care infrastructure is in place, the time is right for the Ministry of Health (MOH) to develop a system to monitor and upgrade the quality of health care services, starting with public sector services. One initiative put forth is health education delivered through various channels, which would make households better aware of the risks associated with certain health conditions or symptoms and the importance of using the available health services from government and NGO facilities. A second type of potential intervention is the introduction of conditional cash transfers, whereby the Government pays a subsidy to households in exchange for certain behaviors beneficial to society, such as having their children immunized. Carrying out the various interventions described above would require that the Government increased its spending on health services further.